Leksem Lidah dalam Peribahasa Melayu Kajian Semantik Inkuisitif - Suhaila, Siti; Hermandra, Hermandra; Permatasari, Silvia (TRANSFORMATIKA, 2024)
Inquisitive semantic study is a study that aims to find out the deeper and broader meaning of a proverb. Through inquisitive semantic study you can also find out what the implied meaning of a proverb is. The tongue is one of the organs in the human body, it is one of the important organs in the human body, if someone does not have a tongue, it will be difficult to speak and convey things. This research aims to explain the meaning and domain of a proverb which has the object of the tongue based on inquisitive semantic studies. The data collection method used was the reading and note-taking method. The data obtained came from the Malay Literature Reference Center. Data analysis was carried out in three stages, namely the first stage of script semantics, the second stage of cognitive semantics, and the final stage of inquisitive semantics. The research results show that Malay proverbs which have the object of the tongue contain many domains, including the domain of caution, the domain of loss, and the domain of futility.